Efeitos da adição de agentes tróficos na dieta de leitões desmamados sobre a expressão da enzima ornitina descarboxilase, os conteúdos de proteína e DNA e o desempenho - Tucci, Fernanda Marcussi; Thomaz, Maria Cristina [UNESP]; Hannas, Melissa Izabel; Scandolera, Antônio João; Budiño, Fábio Enrique Lemos (Universidade Federal de Goiás, 2014)
Two experiments were carried out to evaluate the effect of adding glutamine, fish oil or yeast cellular wall to the diet of weaned piglets on the expression of the enzyme ornithine decarboxylase (ODC), the protein content and DNA in small intestine samples and on performance. In the first experiment, 24 weaned piglets were used to measure the performance at the phases prestarter, starter 1 and starter 2. Four diets were tested (T1 -basal diet (BD); T2 -BD + 1% of glutamine; T3 -BD + 0,2% of yeast cellular wall; T4 -BD + 5% of fish oil). At the second experiment 45 weaned piglets were used and distributed in a randomized block design, in factorial outline with four diets and three slaughter ages (on the day of weaning, on the seventh and fourteenth days postweaning). The tested diets did not alter the piglets' performance in none of the phases. There was reduction of the expression of the ODC enzyme, of the protein concentration and of the relationship protein/DNA to the seven days postweaning, with increase of the values on the 14th day, evidencing a state of hypotrophy of the mucous membrane, suggesting that the process of protein synthesis in the small intestine was diminished in the first week after weaning, but it presented recovery signs in the second week.

Foram conduzidos dois experimentos para avaliar o efeito da adição de glutamina, óleo de peixe ou parede celular de levedura à dieta de leitões desmamados sobre a expressão da enzima ornitina descarboxilase (ODC), o conteúdo de proteína e DNA em amostras de intestino delgado e o desempenho. No primeiro experimento foram utilizados 24 leitões desmamados para medir o desempenho nas fases pré-inicial, inicial 1 e inicial 2. Foram testadas quatro dietas (T1 -dieta basal (DB); T2 - DB + 1% de glutamina; T3 -DB + 0,2% de parede celular de levedura; T4 -DB + 5% de óleo de peixe). No segundo experimento foram utilizados 45 leitões desmamados e distribuídos num delineamento em blocos casualizados, em esquema fatorial, com quatro dietas e três idades de abate (ao desmame, sete e 14 dias pós-desmame). As dietas testadas não alteraram o desempenho dos leitões em nenhuma das fases. Houve redução da expressão da enzima ODC, da concentração de proteína e da relação proteína/DNA aos sete dias pós-desmame, com aumento dos valores aos 14 dias, evidenciando um estado de hipotrofia da mucosa, sugerindo que o processo de síntese protéica no intestino delgado ficou comprometido na primeira semana após o desmame, e apresentou sinais de recuperação na segunda semana.
Effects of the addition of trofic agents in weaned piglets diet on the expression of the enzyme ornithine decarboxylase, on the contents of protein and DNA and on performance
Keywords: Glutamine; Polyunsaturated fatty acids; Prebiotic; swine; Ácidos graxos poliinsaturados; Glutamina; Prebiótico; Suíno